2020
DOI: 10.1017/s1751731120001263
|View full text |Cite
|
Sign up to set email alerts
|

The effect of divergent selection for intramuscular fat on the domestic rabbit genome

Abstract: An experiment of divergent selection for intramuscular fat was carried out at Universitat Politècnica de València. The high response of selection in intramuscular fat content, after nine generations of selection, and a multidimensional scaling analysis showed a high degree of genomic differentiation between the two divergent populations. Therefore, local genomic differences could link genomic regions, encompassing selective sweeps, to the trait used as selection criterion. In this sense, the aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Considering other muscles, selection for intramuscular fat content generated correlated responses also in the biceps femoris , supraspinatus and semimembranosus proprius [ 22 ]. Recent findings have also highlighted that a ten-generation divergent selection for intramuscular fat content produced rabbit populations characterized by a high degree of genomic differentiation, with ten main genes involved and a large polygenic component [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering other muscles, selection for intramuscular fat content generated correlated responses also in the biceps femoris , supraspinatus and semimembranosus proprius [ 22 ]. Recent findings have also highlighted that a ten-generation divergent selection for intramuscular fat content produced rabbit populations characterized by a high degree of genomic differentiation, with ten main genes involved and a large polygenic component [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Divergent lines provide good biological material for genomic studies since they are selected for a unique trait and share the same environment. Previous studies on intramuscular fat (IMF) in rabbits and pigs [ 16 , 29 ], and on antibody response and feather pecking behaviour in chickens [ 30 , 31 ], using divergently selected lines, successfully detected signatures of selection, and identified associated genomic regions. The principal component analysis based on genotype data in our study showed a clear separation between the two divergent rabbit lines (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as each method is based on different assumptions (Fig. 1 ), correlations between results are low [ 15 , 16 ], which makes it difficult to detect overlaps between the identified signatures of selection. The methods used to detect signatures of selection should be considered independently of the sources of QTL detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations